Emphasizing play production concept(s): Relevance and application for student directors in the University of Cape Coast - Koomson, Sika; Boateng, Solomon (International Multidisciplinary Research Journal, 2022)
The relevance of production concept(s) in play production(s) cannot be overemphasized as it forms the theoretical spine for any play production and it informs all the aspects of theatre production. Therefore, the apparent absence of a production concept in any production is problematic; this warrants critical examination. There is a great need to bring the issue of a production concept to student directors if they are to eventually end up as front-runners in theatre practice. Student directors and other budding directors ought to see what lies as the merits and demerits of having a production concept injected into the body of their creative work or not; they also ought to be shown the way in formulating one in the first place as well as how to apply it in their production for the best of results. This paper seeks to examine student directors’ appreciation and application of production concepts for their practical projects at the University of Cape Coast. The aim is to spark a discourse with this subject matter at its core, bridging the gap between it and budding directors for their comprehension, appreciation and application of production concept(s).